Career Development Analysis of SPPG MBG Employees at SPPG Terumbu, Serang City - Septiadi, Deden; Stiawati, Titi; Nurvazria, Vera; Nursyamsi, Amala; Musyarofah, Musyarofah (Future Science, 2026)
This study aims to analyze the implementation of employee career development in improving organizational performance at the Nutrition Fulfillment Service Unit (SPPG) MBG Terumbu, Serang City. Human resources are a strategic factor in determining organizational success, so career development is an important aspect in improving work competence and productivity. This study uses a qualitative method with a descriptive analytical approach. Data collection techniques are carried out through observation and documentation studies related to human resource management and the implementation of Makan Bergizi Gratis (MBG). The results show that employee career development at SPPG MBG Terumbu, Serang City is implemented through training and technical guidance, certification, provision of job opportunities, strengthening managerial capacity, cross-sector collaboration, and workload management. This implementation has been proven to be able to improve employee competence and professionalism. As a result, organizational performance has increased, marked by the effectiveness of service distribution, an increase in the number of SPPG units, flexibility in program implementation, and strengthening the monitoring and public accountability system. Thus, employee career development is a key factor in supporting the success and sustainability of Makan Bergizi Gratis (MBG).